Controlling the narrative: Critiquing the geopolitical narratives of US environmental impact assessments and exclusion of Indigenous communities. Issue 2 (June 2022) - Grote, Katie M
Environmental policy, while often well-intentioned, can fall short when environmental issues intersect with Indigenous community concerns. The intention of the United States National Environmental Policy Act (NEPA) is for federal agencies to consider the adverse environmental impacts prior to action. While NEPA has resulted in some agencies making more environmentally conscious decisions, agency self-interest is sometimes prioritized over socio-ecological well-being. Rather than using environmental impact assessments (EIAs) for their potential to inform just and sustainable environmental decisions, in practice federal, state, and private agencies have the power as assessment document authors to create geopolitical narratives. These narratives can be utilized to legitimize the outcomes that best serve their interests rather than the well-being of the surrounding physical and social environment. This article further explores the details of these narratives through two case studies in which Indigenous communities argued that the EIA documents did not adequately consider their worldviews or holistic adverse impacts. Through the utilization of a case study structure, a qualitative content analysis of EIA documents, and an environmental geopolitics framework informed by Indigenous scholarship, this article illustrates how the EIA process, in its current form, allows for agencies to justify or obscure geopolitically motivated actions, often at the expense of Indigenous communities. This work aims to critically enrich EIA scholarship by exploring the phenomenon of inadequate consideration of Indigenous worldviews through an Indigenous environmental geopolitics framework, building on conceptual understandings of the shortcomings of the EIA process and encouraging changes that make strides toward more equitable environmental assessment practice.